PENGEMBANGAN ALAT UKUR CAREER SATISFACTION PADA KARYAWAN REMOTE WORK - Alghifari, Muhammad Akmal Rifat; Widyowati, Arini (Universitas Gunadarma, 2024)
Today's technological advances enable a variety of people to work from anywhere without being stuck in one place. Career satisfaction becomes a study to see how employees remotely view career satisfaction. The research aims to develop a career satisfaction measure to investigate how a remote employee perceives his or her professional satisfaction. This research uses a quantitative approach with the sampling method used in this research using purposive sampling techniques. The sample in this study is employees who work remotely or can work from anywhere within 200 participants. The data collection uses a career satisfaction scale that has been modified and rearranged by the researchers. Measurement of career satisfaction measurements using confirmatory factor analysis techniques resulted in CFI 0.976, TLI 0.957, and SRMR 0.0254 goodness fit. Then reliability on the scale with the alpha value Cronbach 0.940. In addition, the value of the rest-correlation item ranges from 0.645 to 0.829 with a very good category so that the measurement can measure the level of career satisfaction for employees